2014
DOI: 10.1021/ja4117268
|View full text |Cite
|
Sign up to set email alerts
|

Subnanometer Vacancy Defects Introduced on Graphene by Oxygen Gas

Abstract: The basal plane of graphene has been known to be less reactive than the edges, but some studies observed vacancies in the basal plane after reaction with oxygen gas. Observation of these vacancies has typically been limited to nanometer-scale resolution using microscopic techniques. This work demonstrates the introduction and observation of subnanometer vacancies in the basal plane of graphene by heat treatment in a flow of oxygen gas at low temperature such as 533 K or lower. High-resolution transmission elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(84 citation statements)
references
References 41 publications
4
76
0
1
Order By: Relevance
“…The experimental synthesis of nanoporous graphene has become a subject of tremendous interest [101][102][103]. Achieving highly uniform, subnanometer pores in large-scale sheets of graphene is arguably the most important outstanding goal for the field of NPG membranes, and O'Hern et al have recently produced pores with diameters of (0.40 ± 0.24) nm and densities exceeding 1 × 10 12 cm −2 , while retaining structural integrity of the graphene [8].…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…The experimental synthesis of nanoporous graphene has become a subject of tremendous interest [101][102][103]. Achieving highly uniform, subnanometer pores in large-scale sheets of graphene is arguably the most important outstanding goal for the field of NPG membranes, and O'Hern et al have recently produced pores with diameters of (0.40 ± 0.24) nm and densities exceeding 1 × 10 12 cm −2 , while retaining structural integrity of the graphene [8].…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…In particular, by opportune thermal treatments in controlled atmosphere it has been shown that Gr and also other 2D materials of interest can be doped, but some drawbacks arising from the environment can come including stress effects . In addition, it has been shown that for metal substrate Gr etching could be started as well as in the case of harsh thermal treatments of Gr on dielectric substrates . In this context, a role of molecular water has been evidenced and its interaction with substrate is of particular concern in activating or contrasting the doping .…”
Section: Introductionmentioning
confidence: 99%
“…Graphene and other two-dimensional materials offer a new class of ultrathin membranes that can have atomically defined nanopores with diameters approaching those of hydrated ions [1][2][3][4][5][6][7] . These nanopores have the smallest possible pore volumes of any ion channel, which, due to ionic dehydration 8 and electrokinetic effects 9 , places them in a novel transport regime and allows membranes to be created that combine selective ionic transport 10 with ultimate permeance [11][12][13] and could lead to separations 14,15 and sensing 16 applications.…”
mentioning
confidence: 99%